Decadal variation in the frequency of tropical cyclones originating in the South China Sea and migrating from the western North Pacific - Huang, Peilan; Xu, Jianjun; Liang, Mei (Frontiers in Earth Science, 2022)
A decadal variation in the frequency of tropical cyclones (TCs) that reached their lifetime maximum intensity (LMI) in the South China Sea (SCS; 5°N-25°N, 107°E-121°E) from 1978 to 2020 was identified. TCs that generated and reached LMI in the SCS were named “local TCs,” while those that generated in the western North Pacific (WNP) and reached LMI in the SCS were named “migratory TCs.” A seesaw phenomenon in the frequencies of these two types of TCs was found before and after 1997. From 1978 to 1996, TC frequency was generally lower in local TCs but higher in migratory TCs. The opposite was true from 1997 to 2020. The main factors responsible for this “seesaw” phenomenon include changes in the genesis positions of TCs and the interdecadal variation of large-scale environmental flow patterns. From 1997 to 2020, during which the large-scale steering flow was favorable for local TCs, the monsoon trough over the WNP withdrew westward along with the warm pool and the subtropical high strengthened westward. Meanwhile, the sea surface temperature (SST) gradient between the equator and mid-latitudes decreased and the north wind weakened near 120°E. Easterly winds were strengthened in the equatorial region, which led to an abnormal anticyclone and the divergence of water vapor in the WNP. In contrast, the SST of the SCS, an internal sea, increased significantly. Under local atmosphere-ocean interaction, abnormal cyclonic circulation appeared in the SCS, which led to intensified convergence and intensified wet convection. Changes in the environmental fields in the WNP and SCS are the main reasons for the seesaw phenomenon observed in these two types of TCs.